Colombia: Potential demand for cassava - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
A brief analysis is made of price, commercialization, credit, research, and extension policies and their impact on agriculture in Colombia. The present status of cassava consumption, production, and distribution is then reviewed in order to determine potential and projected demand. Both time series and cross-sectional, household budget data were studied to determine the main parameters influencing cassava consumption. Policies have ignored nontradeables, such as cassava, which cannot compete for resources with more favored crops. Fresh cassava consumption has been adversely affected by rapid urbanization, which has restricted market access and led to higher prices for the consumer. CIAT's new conservation technology can reduce marketing margins for fresh cassava and stabilize prices for producers. Drying cassava, which has just started on a commercial scale, is proving profitable. It is estimated that by the yr 2000, annual requirements for both the fresh and dried market will be almost 600,000 t roots (ca. 60,000 ha at present low yields), which will generate work for ca. 18,000 people. (CIAT)